Via resistance increase accelerated by thermal stress. (May 2021) - Qin, Wentao; Donaldson, Scott; Rogers, Dan; Belisle, Chuck; Grivna, Gordy; Boukhanfra, Lahcen; Thiefain, Julien; Barrientos, Denise; Steinwall, Jim; Chang, George; Gambino, Jeff; Burgin, Rebecca
Abstract: The resistance between an aluminum (Al) metal line and a tungsten (W) via increased after thermal stress. In the wafer processing, the post W chemical mechanical planarization (WCMP) cleaning left residual WO3 on the W plug. Since the resistivity of WO3 is low, the interfacial resistance was low and escaped the first electrical detection. However, the WO3 was spontaneously reduced by the Ti of the overlaying metal line, through which TiO2 formed. The reduction was accelerated by a thermal stress. Compared with WO3, TiO2 has a more negative formation enthalpy, and the valence electrons of Ti are more tightly bound to the O ion cores. As a result, the resistivity of TiO2 is higher than that of WO3 . In addition, there was Al diffusing through TiN to reduce the oxides of both Ti and W. The product Al2 O3 is thermodynamically the most stable, and the most resistive amongst the oxides of the three metals. Meanwhile, due to its superhydrophilicity, the residual WO3 had retained liquid that contained hydrofluoric acid (HF) used for the post WCMP cleaning. The HF corroded the Ti glue layers of both the via sidewall and the overlaying metal line. The dry etch of the metal line exposed the Ti-corroded volume of the metal line to the deionized (DI) water for the post metal-etch cleaning. The DI water oxidized the Ti on the W plug. The W/TiN interface on the W plug was also subjected to enhanced mechanical stress which led to voids along the interface. All these factors had caused an increase of the via resistance which eventually became high enough to be detected. The fix employed was to increase the NH4 OH concentration to more effectively remove the residual WO3 . The thermal stress implemented in the fab therefore had prevented the residual WO3 from developing into a costly field failure. Graphical abstract: Unlabelled Image Highlights: Residual WO3 on W plug. Via resistance was low and passed electrical testing. Ti reduced WO3, Al reduced oxides of Ti and W, to produce TiO2 and Al2 O3 . Both reductions were accelerated thermally. Thermodynamic stabilities and electrical resistivities are ranked as Al2 O3 > TiO2 > WO3 . Via resistance increased due to the oxide phase changes and voiding at the interface. Device failed. NH4 OH concentration was increased to remove WO3 and solve the problem.